CO2 dissociation using the Versatile atmospheric dielectric barrier discharge experiment (VADER) - Lindon, Michael A.; Scime, Earl E. (Frontiers in Physics, 2014)
Dissociation of CO2 is investigated in an atmospheric pressure dielectric barrier discharge (DBD) with a simple, zero dimensional (0-D) chemical model and through experiment. The model predicts that the primary CO2 dissociation pathway within a DBD is electron impact dissociation and electron-vibrational excitation. The relaxation kinetics following dissociation are dominated by atomic oxygen chemistry. The experiments included investigating the energy efficiencies and dissociation rates of CO2 within a planar DBD, while the gas flow rate, voltage, gas composition, driving frequency, catalyst, and pulse modes were varied. Some of the VADER results include a maximum CO2 dissociation energy efficiency of 2.5 ± 0.5%, a maximum CO2 dissociation rate of 4 ± 0.4 ×10−6 mol CO2/s (5 ± 0.5% percent dissociation), discovering that a resonant driving frequency of 30 kHz, dependent on both applied voltage and breakdown voltage, is best for efficient CO2 dissociation and that TiO2, a photocatalyst, improved dissociation efficiencies by an average of 18% at driving frequencies above 5 kHz.